2024
DOI: 10.1098/rsfs.2023.0072
|View full text |Cite
|
Sign up to set email alerts
|

Stiff morphing composite beams inspired from fish fins

Saurabh Das,
Prashant Kunjam,
Baptiste Moling
et al.

Abstract: Morphing materials are typically either very compliant to achieve large shape changes or very stiff but with small shape changes that require large actuation forces. Interestingly, fish fins overcome these limitations: fish fins do not contain muscles, yet they can change the shape of their fins with high precision and speed while producing large hydrodynamic forces without collapsing. Here, we present a ‘stiff’ morphing beam inspired from the individual rays in natural fish fins. These synthetic rays are made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The following study by Das et al . [ 8 ] introduces a synthetic morphing beam inspired by natural fish fins, comprising acrylic outer beams connected by highly compliant rubber ligaments. Through experiments and modelling, it is demonstrated that the ligaments exhibit nonlinear geometrical effects, enhancing the stability of the beam at large deformations while remaining mechanically invisible at small deformations, providing insights for optimizing morphing shape and stiffness in bioinspired structures for diverse applications in aerospace, biomedicine, and robotics.…”
mentioning
confidence: 99%
“…The following study by Das et al . [ 8 ] introduces a synthetic morphing beam inspired by natural fish fins, comprising acrylic outer beams connected by highly compliant rubber ligaments. Through experiments and modelling, it is demonstrated that the ligaments exhibit nonlinear geometrical effects, enhancing the stability of the beam at large deformations while remaining mechanically invisible at small deformations, providing insights for optimizing morphing shape and stiffness in bioinspired structures for diverse applications in aerospace, biomedicine, and robotics.…”
mentioning
confidence: 99%